Examining the incidence of acute stress in pediatric trauma patients. Issue 1 (17th August 2022) - Schauss, Eraina; Hawes, Kiersten; Roberts, Sydnie; Clayton, Joseph Mitchell; Li, Chi; Littlejohn, Alexandria; Bartelli, Debra; Williams, Regan
Abstract : Objective: Pediatric patients can be significantly impacted emotionally by exposure to acute trauma which may negatively impact long-term functioning and lead to an increase in overall distress. This study reports on the incidence of acute stress disorder among pediatric trauma patients in a hospital setting in the southeastern region of the USA. Methods: Pediatric patient mental health assessments were conducted using the Childhood Stress Disorders Checklist- Short Form (CSDC-SF) as part of a new integrated behavioral health standard of care within the Trauma Services Division of a level 1 pediatric hospital. Mental health consultations occurred at bedside on inpatient hospital admission into trauma services, or at the outpatient hospital clinic after discharge for injuries treated in the emergency department. Results: Associations among type of trauma, child age, and sex were explored in a sample of 617 children (58.9% male) aged 2–18 years ( M age =10.27). The sample was primarily ethnic minorities (56.1% black/African-American, 5% Hispanic/Latinx). Fifteen per cent or more of trauma reports were for burns (26%), motor vehicle accident (22.7%), and recreational sports or leisure activity-related injury (17.5%). Sixty-four per cent of children scored ≥1 on the CSDC-SF, indicating symptoms consistent with acute stress disorder. Higher scores were associated with female sex, age, and injury type. Level of evidence: Level IV study provides evidence of the link between traumatic injury and mental health symptoms in a pediatric population. Findings highlight the critical need for mental health screening and provision of integrated mental health counseling services at time of acute pediatric trauma.